Inequality of opportunity in higher education in the Middle East and North Africa. (September 2018) - Krafft, Caroline; Alawode, Halimat
Highlights: This paper explores inequality in higher education in Egypt, Jordan, and Tunisia. We find that inequality is high in Egypt and Tunisia, but moderate in Jordan. Family socio-economic characteristics are the primary driver of inequality. Background affects attainment directly and indirectly, through test scores. Public spending on higher education is regressive and may increase inequality. Abstract: Struggles with inequality have been prominent in the Middle East and North Africa in the aftermath of the Arab Spring. This paper examines the extent and drivers of inequality of opportunity in attaining higher education in Egypt, Jordan, and Tunisia. We find that inequality is similarly high in Egypt and Tunisia, but moderate in Jordan. Background characteristics affect attainment even after accounting for test scores, which are themselves influenced by background. Particularly in Egypt and Tunisia, where higher education is free of charge, public spending on higher education is regressive. Thus, a theoretically meritocratic and equitable system perpetuates inequality.